Inhibition of Granule Cell Dispersion and Seizure Development by Astrocyte Elevated Gene-1 in a Mouse Model of Temporal Lobe Epilepsy - Eunju Leem; Sehwan Kim; Chanchal Sharma; Youngpyo Nam; Tae Yeon Kim; Minsang Shin; Seok-Geun Lee; Jaekwang Kim; Sang Ryong Kim (Biomolecules, 2024)
Although granule cell dispersion (GCD) in the hippocampus is known to be an important feature associated with epileptic seizures in temporal lobe epilepsy (TLE), the endogenous molecules that regulate GCD are largely unknown. In the present study, we have examined whether there is any change in AEG-1 expression in the hippocampus of a kainic acid (KA)-induced mouse model of TLE. In addition, we have investigated whether the modulation of astrocyte elevated gene-1 (AEG-1) expression in the dentate gyrus (DG) by intracranial injection of adeno-associated virus 1 (AAV1) influences pathological phenotypes such as GCD formation and seizure susceptibility in a KA-treated mouse. We have identified that the protein expression of AEG-1 is upregulated in the DG of a KA-induced mouse model of TLE. We further demonstrated that AEG-1 upregulation by AAV1 delivery in the DG-induced anticonvulsant activities such as the delay of seizure onset and inhibition of spontaneous recurrent seizures (SRS) through GCD suppression in the mouse model of TLE, while the inhibition of AEG-1 expression increased susceptibility to seizures. The present observations suggest that AEG-1 is a potent regulator of GCD formation and seizure development associated with TLE, and the significant induction of AEG-1 in the DG may have therapeutic potential against epilepsy.